HISTORICAL AND PEDAGOGICAL, COMPARATIVE ASPECTS OF THE EMERGENCE AND DEVELOPMENT OF STEM EDUCATION - Батюк, Лілія (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
The article examines the historical and pedagogical, comparative aspects of the emergence and development of STEM education and integration of STEM education into the educational environment of the USA and Ukraine at the level of schools, colleges and universities. The implementation of the study involved the implementation of a number of tasks: to characterize the source of origin and the state of the concept of STEM education; to reveal the conceptual foundations and genesis of the formation of STEM education in the educational environment of the USA and Ukraine; to outline the regulatory and content-procedural principles of STEM education in the USA and Ukrain; to find out the current state of STEM education in Ukraine and identify opportunities to use the progressive experience of US STEM education in Ukraine. To solve the tasks set, documents, laws and regulatory materials were studied that determine the content of STEM education in the USA and Ukraine; archival materials and documents of the White House and the US Congress were studied; analysis and synthesis of search results in information sources were carried out. It is found that the US Federal, state and local governments, and the private sector, have taken on the responsibility of improving the educational environment by providing educators with the opportunity to receive STEM education, to participate in educational programs that are determined by the Government. STEM educational system curricula play a significant role for the United States, preparing students and teachers for careers in STEM, by increasing the global competitiveness of the United States. The article provides useful context about the American STEM education system based on the research question; summarizes selected major laws that have influenced American STEM education. The article outlines the structure of STEM comepetence and skills, which are increasingly combined with the promotion of interdisciplinary approaches to teaching and learning. The article describes the time periods, emergence and development of STEM education; gives examples of the use of STEM education at the international level, and was considered the possibilities of scientific, technical, engineering and mathematical education of citizens in the field of STEM. The history of the spread of STEM educational innovations in the education sector of Ukraine is examined.